Iodine-Mediated Multicomponent Synthesis of 3-Sulfenylimidazo[1,2-a]pyridines from 2-Aminopyridines, Ketones, and Sulfonyl Hydrazides - Hu, Sipei; Du, Shiying; Yao, Yunjie; Yang, Zuguang; Ren, Hongjun; Chen, Zhengkai (Synlett, 2019)
A one-pot multicomponent reaction for the synthesis of 3-sulfenylimidazo[1,2-a]pyridines from readily available 2-aminopyridines, ketones, and sulfonyl hydrazides, mediated by molecular iodine, has been developed. The transformations proceed smoothly with high efficiency and a broad substrate scope, affording the desired heterocyclic products in moderate to excellent yields.
Keywords: metal-free synthesis; multicomponent reaction; C–S bond formation; imidazopyridines; N-heterocyclic compounds